They Saw It Coming: Rising Trends in Depression, Anxiety, and Suicidality in Creative Students and Potential Impact of the COVID-19 Crisis - Kerr, Barbara A.; Birdnow, Maxwell; Wright, Jonathan Daniel; Fiene, Sara (Frontiers in Psychology, 2021)
Previous research has established that creative adolescents are generally low in neuroticism and as well-adjusted as their peers. From 2006 to 2013, data from cohorts of creative adolescents attending a counseling laboratory supported these results. Clinical findings of increased anxiety, depression, and suicidality among creative students in 2014 led the researchers to create 3 studies to explore these clinical findings. Once artifactual causes of these changes were ruled out, a quantitative study was conducted. Study 1, an analysis of mean differences of pre-2014 and post-2014 cohorts showed that post-2014 cohorts scored significantly higher in Neuroticism, Openness to Experience, and Conscientiousness and lower in Extraversion on Big 5 inventories. Regression analyses suggested that while Neuroticism was associated with gender, Conscientiousness and Grade Point Average for the earlier group, Neuroticism in the post 2014 groups was related to complex interplay of all personality dynamics except Agreeableness. In the qualitative Study 2, focus groups of 6–10 students, for a total of 102 participants were queried about the reasons they perceived for increased anxiety and depression in creative students. Increased achievement pressures and awareness of environmental and social problems were major sources of external stressors; perfectionism and desire to fulfill expectations of others were the primary sources of internal stress. The authors suggest that creative students' openness to experience and advanced knowledge made it possible for these students to see the potential for environmental and social crises and respond to their inability to solve these problems with anxiety and depression. Study 3 was a qualitative study that followed up 19 participants from the post-2014 cohort to explore the impact of the COVID-19 pandemic on mental health and creativity. While the majority perceived a negative effect of the pandemic on their mental health, most also produced a surprising variety of creative works during that time. In conclusion, rapid changes in the lives of creative adolescents since 2014 suggest that scholars focus on current cohorts and the ways in which adolescent personality is shaped by internal expectation and external pressures and global events. Despite the pandemic, creative young people continued to create.